Digital Literacy with Software Media Application of Elementary Social Studies Materials to Improve Student Learning Outcomes - Rifayanti, Zuni Eka Tiyas; Salamah, Evi Rizqi (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
The development of technology is currently growing so much, especially the existing software, individuals must understand that digital literacy is a necessity to participate in the modern world. Digital literacy is as important as reading, writing and arithmetic. The Ministr y of Education and Culture in 2017 promoted the digital literacy movement in elementary schools in the form of; the number and variety of reading materials and visual aids, the frequency of borrowing books, the number of activities at school, presentation of school information, school policies, communication within the school environment, as well as the use and application of information technology in the form of e-reports, financial management, dapodik, utilization of student data, all school profiles are packaged in the form of digital technology. Through this movement, researchers utilized application software in the form of social studies SD learning applications, to support digital literacy activities in elementary schools. The purpose of this study is to provide recommendations for digital-based learning media in the form of social studies SD learning applications as a support for the digital literacy movement, and provide solutions to improve student learning outcomes, especially in social studies SD.